Wind power estimation on local scale—A case study of representativeness of reanalysis data and data-driven analysis - Schicker, Irene; Ganglbauer, Johanna; Dabernig, Markus; Nacht, Thomas (Frontiers in Climate, 2023)
With hydropower being the dominant source of renewable energy in Austria and recent years being disproportionally dry, alternative renewable energy sources need to be tapped to compensate the reduction of fossil fuels and account for dry conditions, this : . ::::: This : becomes even more important given the current geo-political situation. Wind power plays an essential role in decarbonising Austria's electricity system. For local assessment of historic, recent, and future wind conditions, adequate climate data is essential. Reanalysis data, often used for such assessments, has a coarse spatial resolution and could be unable to capture local wind features, relevant for wind power modelling. Thus, raw reanalysis data need some sort of post-processing and results need to be interpreted with care.The purpose of this study is to assess the quality of three reanalysis data sets, MERRA-2, ERA5, and COSMO-REA6, for both surface level and hub height wind speed and wind power production at meteorological observation sites and wind farms in flat and mountainous terrain. :: A